Estimation of gingival crevicular fluid oxidative stress markers in school-aged children and teenagers with insufficient sleep - Qianwen Yin; Chao Liu; Han Bao; Size Li; Zhuwei Huang; Deao Gu; Liping Xiong; Leiying Miao (BMC, 2022)
Abstract Background Sleep is crucial for survival. Sleep deprivation causes ROS accumulation and, consequently, oxidative stress. The goal of the study was to evaluate gingival crevicular fluid (GCF) levels of the oxidative stress status hydrogen peroxide (H2O2), superoxide glutathione (GSH), and cellular oxidative damage marker malondialdehyde (MDA) in school-aged children and teenagers with insufficient sleep. Methods This study investigated sleep duration in 80 participants from two different developmental stages: school-aged children (6-13 years) and teenagers (14-17 years). GCF samples were obtained from all individuals, and samples were investigated to detect H2O2, GSH, and MDA levels using the micro method. Results Results reveal that GCF MDA and H2O2 in school-age children and teenagers with insufficient sleep were significantly higher than in children with sufficient sleep. GCF GSH with insufficient sleep was insignificantly lower than in children with sufficient sleep. There was no significant difference between school-age and teenage populations. Conclusion Sleep deprivation causes increased levels of oxidative stress in gingival crevicular fluid, and adequate sleep is essential for maintaining redox balance.